Peningkatan Pemasaran Produk melalui Marketing Digital pada Grace Konveksi - I Gede Putra Mas Yusadara; IGKG Puritan Wijaya ADH; Dewa Ayu Mirnawati; Sevany Primantara; Made Jiyestha Darmika Putra (Insan Kreasi Media, 2026)
Grace convection is a garment manufacturing business in Denpasar that uses a manual ordering process. Problems arising from this manual process are often time-consuming and prone to missed orders. This community service program aims to improve digital marketing while streamlining the ordering process for easier monitoring by partners. The method used in implementing this service is Participatory Action Research, which begins with a survey, FGDs, and then implementing a website as a marketing and ordering medium. The results of the activity indicate that partners have established a business profile website and catalog. Partners can understand the ordering process, starting with preparing more consistent digital content to support digital channels. Through this system, ordering becomes more structured and the capacity of partners in managing activity content is maximized, strengthening Grace convection's readiness to expand its market segmentation reach.